The Relation of TMJ Disorders with Stress Level and Blood Groups among Dental Students in Baghdad, Iraq - Malath Nabil Jafar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: TMDs are a common group of disorders that affect approximately 60–70% of the general population. The aim of current study is to find out the association between TMJ disorders with stress levels and blood groups among dental students in Baghdad, Iraq. Methods: A cross-sectional study was conducted among 60 dental students in Baghdad, Iraq using convivence sampling method. Perceived stress scale questionnaires were used to measure stress level among respondents. Results: The majority of respondents had a headache (55.0%), with pain (28.3%), clicking (45.0%) and bruxism (31.7%). Regarding bad habits, only (23.3%) had bad habits. There was a significant association between TMJ Pain, Bruxism and stress level with P value (0.016, 0.02) respectively. Also, there was a significant association between bruxism and blood group type with P value (0.014). Conclusion: There was a significant association between TMJ disorders (pain, bruxism) with stress level and also between bruxism and blood group types. More education and promotion are needed regarding TMJ disorders and how to deal with complications especially among young adults like university students.